The Effect of Fun Cooking (Blue Rice) Activities on the Intrapersonal Intelligence of Kindergarten B1 Children at Islam Al-Fatah Surabaya - Kanaya, Salisa; Rinakit, Kartika; Safitri, Dhian Gowinda Luh (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aimed to determine the effect of Fun Cooking activities on the intrapersonal intelligence of children aged 5–6 years in class B1 at TK Islam Al-Fatah Surabaya. The research employed a pre-experimental design with a one-group pretest–posttest model. A total of 14 children were involved as research subjects. Data collection was conducted through a pretest, two treatment sessions using Fun Cooking (Blue Rice), and a posttest. The instrument used consisted of five items, all of which were declared valid and reliable with a Cronbach’s Alpha value of 0.812. Data were analyzed using the Wilcoxon Signed Rank Test with SPSS version 21. The results showed significant differences between the pretest and posttest, as well as between the two treatment sessions, with Asymp. Sig. (2-tailed) < 0.05. These findings indicate that Fun Cooking activities are effective in improving the intrapersonal intelligence of early childhood and can be used as an innovative learning alternative.